Prevalence of frailty and its effect on requirement of organ support and clinical outcomes in critically ill patients: a prospective observational single center study - Dhananjay Kumar Singh; Venkata Ganesh; Neeru Sahni; Balaji Kannamani; Vikas Saini; Laxminarayana Yaddanapudi (BMC Anesthesiology)
Abstract Background Assessing pre-hospital frailty on ICU admission can help in risk stratification. We conducted this prospective, observational study to determine the prevalence of frailty in critically ill patients based on Clinical Frailty Scale (CFS) within 24 h of admission and to study effect of frailty on requirement of organ support and clinical outcome. Methods The study was registered in Clinical Trials Registry-India (CTRI/2021/04/032782) on 13/04/2021. After approval from IEC and written informed consent, all adult patients admitted to our ICU from April 15th, 2021 to April 14th, 2022 were included. The patients were categorized as Frail & Non-Frail, defining frailty as CFS ≥ 5, two weeks before index admission. The groups were compared for requirement of organ support (vasoactive support, mechanical ventilation, renal replacement therapy) and clinical outcomes (hospital acquired infections (HAI), hospital and ICU length of stay (LOS) and hospital, ICU and 30-day mortality). Result Out of 358 admissions, 317 were enrolled. The demographic data were comparable except for higher family income amongst frail patients, p < 0.001. The prevalence of frailty was 24.6%. A significantly higher number of frail patients required vasoactive support (p = 0.006). Incidence of HAI in frail group was significantly higher (48.7%) as compared to non-frail group (20.9%) (p < 0.001). The median ICU LOS was 7 days [IQR, 3–7] in frail compared to 6 days [IQR,3–10] in non-frail group, p = 0.051. The median hospital LOS in frail patients was 18 days [IQR,10–32] compared to 15 days [IQR, 8.25-26] in non-frail, p = 0.005. ICU, hospital and 30-day mortality were significantly higher in frail patients, p < 0.01. Conclusion The prevalence of frailty in ICU patients was 24.6% and a higher number of frail patients had requirement of vasopressor support and incidence of HAI. Additionally, frail patients also had longer hospital LOS and higher ICU, hospital and 30-day mortality. Trial registration CTRI/2021/04/032782.